Supporting the parents of children and young people with anxiety and depressive disorders is an opportunity not to be missed: a scoping review - Lawrence, PJ; Parkinson, M; Jasper, B; Creswell, C; Halligan, SL (Elsevier, 2021)
Guidance is scarce on whether and how to involve parents in treatment for anxiety and depressive disorders in children and young people. We did a scoping review of randomised controlled trials of psychological interventions for anxiety and depressive disorders in children and young people, in which parents were involved in treatment, to identify how parents and carers have been involved in such treatments, how this relates to both child and broader outcomes, and where research should focus. We identified 73 trials: 62 focused on anxiety and 11 on depressive disorders. How parents were involved in treatments varied greatly, with at least 13 different combinations of ways of involving parents in the anxiety trials and seven different combinations in the depression trials. Including parents in treatment did not impair children's and young people's outcomes, but the wide variability in how they were involved prevents clarity about why some trials favoured parent involvement and others did not. Studies must consider the long-term and wider benefits beyond children's and young people's mental health, such as enhanced engagement, family wellbeing, and economic gains.